2021
DOI: 10.1038/s41467-021-26338-0
|View full text |Cite
|
Sign up to set email alerts
|

Mid-lateral cerebellar complex spikes encode multiple independent reward-related signals during reinforcement learning

Abstract: Although the cerebellum has been implicated in simple reward-based learning recently, the role of complex spikes (CS) and simple spikes (SS), their interaction and their relationship to complex reinforcement learning and decision making is still unclear. Here we show that in a context where a non-human primate learned to make novel visuomotor associations, classifying CS responses based on their SS properties revealed distinct cell-type specific encoding of the probability of failure after the stimulus onset a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…These results demonstrated that the cerebellum reduces dimensions of activity in a large number of neurons to a much smaller number of components, each of which is driven by a synchronization scheme that conforms to a specific task. Interestingly, we also found that individual anatomical zones and even a single CF could contain signals from multiple components [53][54][55][56] .This study provided the first evidence simultaneously supporting the two major theories of cerebellar functions in a single task 18,[57][58][59][60][61][62] , and should contribute to resolution of the longstanding controversy 63 . This study also unveiled the secret of cerebellar functional architecture: learning from small samples is achieved by compartmentalization (reduced degrees of freedom) due to synchronization and dynamics; therefore, it may contribute to new-generation AI designs.…”
supporting
confidence: 57%
“…These results demonstrated that the cerebellum reduces dimensions of activity in a large number of neurons to a much smaller number of components, each of which is driven by a synchronization scheme that conforms to a specific task. Interestingly, we also found that individual anatomical zones and even a single CF could contain signals from multiple components [53][54][55][56] .This study provided the first evidence simultaneously supporting the two major theories of cerebellar functions in a single task 18,[57][58][59][60][61][62] , and should contribute to resolution of the longstanding controversy 63 . This study also unveiled the secret of cerebellar functional architecture: learning from small samples is achieved by compartmentalization (reduced degrees of freedom) due to synchronization and dynamics; therefore, it may contribute to new-generation AI designs.…”
supporting
confidence: 57%
“…A hallmark of the previously reported reward-based error signal was that it was unlikely to be driven by complex spike activity (Sendhilnathan et al, , 2021. Here, too, the concurrent complex spike activity was unlikely to have caused these changes in simple spike activity (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…8E). This suggests that there is no obvious relationship between simple spike and complex spike activity during reward-based learning (Larry et al, 2019;Sendhilnathan et al, 2021). and that the complex spike responses did not affect the simple spike activity or the behavior through an error-based learning mechanism.…”
Section: Complex Spikes Did Not Instruct Changes In Simple Spike Neur...mentioning
confidence: 98%
See 1 more Smart Citation
“…Rodent studies showed cocaine-paired olfactory cue increased activity of the granule cell layer of the cerebellar vermis (Carbo-Gas, Vazquez-Sanroman, Aguirre-Manzo, et al, 2014; Carbo-Gas, Vazquez-Sanroman, Gil-Miravet, et al, 2014), and a random cocaine-odour pairing procedure triggered higher cFos expression in the Med (Carbo-Gas, Vazquez-Sanroman, Gil-Miravet, et al, 2014). Non-human primate PCs encoded multiple independent reward-related signals during reinforcement learning (Sendhilnathan, Ipata, & Goldberg, 2021). Here, we found Med CaMKII neurons were notably excited during CPP training, but not CPP test, suggesting Med glutamatergic neurons are responsive to METH instead of METH-paired conditioned stimulus.…”
Section: Discussionmentioning
confidence: 99%